Cognitive processing patterns in the production of metaphors by in-service teachers in the sciences and social sciences. - Gopal, Manjari. (University of Ottawa (Canada), 1993)
The purpose of this exploratory study is primarily to identify and examine the processes and patterns that are employed by Secondary and Intermediate school teachers in the production of metaphors. The research objectives that were explicitly explored were: (1) the examination of the characteristics of the statements produced as metaphorical descriptions by Secondary and Intermediate school teachers. (2) the exploration of the differentiating characteristics of the statements that discriminate between the Secondary and Intermediate school teachers across gender and domain of specialization. (3) the identification of the cognitive processes that were employed in the production of metaphors by groups of Secondary and Intermediate school teachers differentiated by gender and specialization. (4) the identification of the distribution patterns of cognitive activity or global strategies that were observed for the groups of Secondary and Intermediate school teachers, differentiated by gender and domain of specialization. The development of a coding grid for idenfying the cognitive processes utilized by the participants help in the categorization of the data into 29 activities grouped into six episodes. A classification scheme to examine the nature of the descriptive statements made provides three types of statements (Structural, Functional and Evaluative), that are analyzed for five levels of complexity of mapping (ranging from Basic to Complex). The categorization of the cognitive processes utilizing the specific coding grid developed and the classification of the metaphorical statements are qualitatively analysed. This is followed by a quantitative analysis of the stimulus-topics and the targets which are further analyzed for patterns of observations across gender and specialization. While some differences in the categories of statements produced can be ascribed to gender and specialization differences, other variables that influenced the task performance were contextual. The format of presentation of stimulus-topics (visual-verbal) and the types of verbal stimuli presented: abstract and concrete forms of nouns and adjectives affected the types of "targets" used and also the types and categories of statements produced. The frequency and duration of episodes were extracted through 'process strips' to analyse the distributions of occurrences. "Participant profiles" that show the global strategies used by each participant are then obtained. These profiles can be used as a diagnostic tool in the classroom since it can help in the identification of the weaknesses and strengths in an individual's profile, particularly when the absence or limited use of certain cognitive activity is observed in the profile. Intervention measures can be planned to remedy and compensate for any limitations in processing activity observed in the profiles. Other implications of this study include the recognition of the important role played by personal experiences for producing figurative language. The need to include the students own experience in the classroom are stressed. (Abstract shortened by UMI.)
Keywords: Education, Secondary.